Peranan Keluarga Samawa dalam Pelaksanaan Pendidikan Agama Islam - Dede Husni Mubarrak (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2016)
The writer argues that ini Islam which is based on the Holy al-Qur’an and al-Sunnah ideal (sakinah) family is designated by a composure, peaceful. And happiness life which is simplified in a fully love and affection relationship between husband and wife. Such a family needs a commitmen to: (1) goal, (2) intention, (3) exertion, and (4) the quality of the family. In practice, sakinah family will not be achieved without a well practice of religion.